ABO‐incompatible deceased donor pediatric liver transplantation: Novel titer‐based management protocol and outcomes. (2nd August 2018) - Mysore, Krupa R.; Himes, Ryan W.; Rana, Abbas; Teruya, Jun; Desai, Moreshwar S.; Srivaths, Poyyapakkam R.; Zaruca, Kimberly; Calvert, Andrea; Guffey, Danielle; Minard, Charles G.; Morita, Eda; Hensch, Lisa; et al.
Abstract: ABO‐ILT have re‐emerged as an alternate option for select patients awaiting transplant. However, treatment protocols for children undergoing deceased donor ABO‐ILT are not standardized. We implemented a novel IS protocol for children undergoing deceased donor ABO‐ILT based on pretransplant IH titers. Children with high pretransplant IH titers (≥1:32) underwent an enhanced IS protocol including plasmapheresis, rituximab, IVIG, and mycophenolate, while children with IH titers ≤1:16 received steroids and tacrolimus. We retrospectively assessed our outcomes of ABO‐ILT with ABO‐compatible recipients of similar age and diagnosis over a 2‐year period. Ten children with median age of 8.9 months underwent ABO‐ILT, 4 of 10 patients underwent enhanced IS due to high IH titers. Rates of complications (rejection, infections, biliary, and vascular) at both 1 year and up to 3 years post‐transplant were comparable between the groups. Patients with ABO‐ILT had good graft function with 100% survival at a median follow‐up of 3.3 years. In conclusion, IS tailored to pretransplant IH titers in pediatric deceased donor ABO‐ILT is feasible and can achieve outcomes similar to ABO‐CLT at 1 and 3 years post‐transplantation.